Measuring China’s Policy Stringency on Climate Change for 1954–2022 - Bo Li; Enxian Fu; Shuhao Yang; Jiaying Lin; Wei Zhang; Jian Zhang; Yaling Lu; Jiantong Wang; Hongqiang Jiang (Scientific Data)
Abstract Efforts on climate change have demonstrated tangible impacts through various actions and policies. However, a significant knowledge gap remains: comparing the stringency of climate change policies over time or across jurisdictions is challenging due to ambiguous definitions, the lack of a unified assessment framework, complex causal effects, and the difficulty in achieving effective measurement. Furthermore, China’s climate governance is expected to address multiple objectives by integrating main effects and side effects, to achieve synergies that encompass environmental, economic, and social impacts. This paper employs an integrated framework comprising lexicon, text analysis, machine learning, and large-language model applied to multi-source data to quantify China’s policy stringency on climate change (PSCC) from 1954 to 2022. To achieve effective, robust, and explainable measurement, Chain-of-Thought and SHAP analysis are integrated into the framework. By framing the PSCC on varied sub-dimensions covering mitigation, adaptation, implementation, and spatial difference, this dataset maps the government’s varied stringency on climate change and can be used as a robust variable to support a series of downstream causal analysis.